Efektivitas Pendampingan Kesehatan Reproduksi pada Santriwati di LKSA Putri Aisyiyah Ngawen Klaten - Wardojo, Sri sunaringsih ika; Rosadi, Rakhmad; Rahmanto, Safun (Sinesia : Jurnal Pengabdian Masyarakat, 2024)
Adolescent health is very important to pay attention to because during this period, adolescents experience very significant physical, psychological, and social changes. The background of the community service program at an orphanage called LKSA Putri Aisyiyah Ngawen is because based on the results of observations, there is still a lack of knowledge of orphans’ female students regarding their reproductive health, in addition, the lack of knowledge of orphanage caregivers about reproductive health so that health coaching is considered less than optimal, which affects the quality of health of among their orphanage children. The implementation of education at orphanage is important to implement, especially providing education to female students so that they can become pioneers in increasing awareness, changing behavior and peer educators in efforts to improve health in the orphanage environment. Education was carried out at orphanage with 30 female students who lived in the orphanage as participants. The method used was counseling with evaluation in the form of pre-test and post-test. The material provided includes the definition of reproductive health, types of diseases related to reproductive health, as well as steps and benefits of maintaining personal hygiene in adolescents which are divided into two sessions and followed by Q&A. The results showed that the education provided was able to increase the knowledge of female students at LKSA Putri Aisyiyah Ngawen Klaten regarding reproductive health.